THE "CLI-FI" AND THE ECOCRITICAL IN MARGARET ATWOOD'S ECOPOETRY - Inas Samy Abolfotoh (European Scientific Journal, ESJ, 2015)
Ecocriticism is commonly associated in canonical circles with many names like John Muir, Henry David Thoreau, Aldo Leopold, Ralph Emerson, and other American pioneer ecophilosophers. However, this paper argues that Margaret Atwood is one of the assured ecocritical pioneer voices whose environmental insights have been marginalized in favour of an exceptional focus on her Feminist pioneering radical writings. Atwood, the paper proposes, has been poetically tackling many of the current ecological crises since about 30 years before the final coinage of Ecocrticism in the 1990s. As a matter of fact, Atwood has not only been marginalized as an ecophilosopher, but also as a poet. She is commonly identified as a prominent novelist and generally under-analyzed as a poet. Atwood has written 12 poetry books covering versatile issues and themes just like her novels. The present paper sheds light on both Atwood, the ecophilosopher, and Atwood, the poet. Her Ecopoetry envelops various ecocritical fields. Nevertheless, the research will concentrate on her interest in the mounting climate change that shows up clearly in a number of jeremiadic poems due to anthropocentric violations against Nature.